Oncological and Functional Outcomes after Hemicortical Resection and Biological Reconstruction Using Allograft for Parosteal Osteosarcoma of the Distal Femur. (2nd June 2022) - Savvidou, Olga D; Goumenos, Stavros; Trikoupis, Ioannis; Kaspiris, Angelos; Melissaridou, Dimitra; Gavriil, Panagiotis; Georgoulis, Jimmy; Papagelopoulos, Panayiotis J
Abstract : Background . Parosteal osteosarcoma (PAOS) is a surface osteosarcoma. Treatment options include wide excision and endoprosthetic or allograft. However, due to the low local recurrence and metastasis rate, when it appears in the posterior surface of the distal femur, the lesion can be managed with hemicortical wide resection and biological reconstruction with hemicortical allograft. The purpose of this study is to evaluate the oncological and functional outcomes of patients with parosteal osteosarcoma (PAOS) of the posterior cortex of the distal femur who underwent biological reconstruction after hemicortical resection. Methods . Eleven patients who underwent wide tumor resection and defect reconstruction of the posterior surface of the distal femur using hemicortical allograft were retrospectively studied. Local recurrence, metastasis, complications, and the functional outcome using the Musculoskeletal Tumor Society (MSTS) scoring system were evaluated. Results . The average postoperative follow-up period was 53.64 months (range, 30 to 84 months). At the latest follow-up, all patients had no evidence of disease without metastases. One patient with local recurrence underwent revision surgery with fibula autograft reconstruction. The mean MSTS score was 93.45 ± 3.56. Conclusions . Treatment of patients with PAOS of the posterior aspect of the distal femur with hemicortical resection and allograft reconstruction has satisfactory oncological and functional outcome and low complication rates.